THE PROSPECT OF GROWING SAFFLOWER IN KAZAKHSTAN - Zhambakin , K.J.; Shamekova , M.H.; Volkov , D.V.; Zatybekov , A.K. (Eurasian Journal of Applied Biotechnology, 2014)
Commercial cultivation of safflower appeal lies in its high resistance to drought and high quality of the oil obtained. At the same time, despite the fact that safflower has been known since antiquity, this culture is still poorly understood. Safflower highly varies in morphology, content and composition of the oil, depending on the region of cultivation. The review provides data on the use of safflower as a plant for multipurpose use in food industry, medicine and as a food source for animals and birds. Demand for safflower oil has been increasing over the last period due to the high level content of polyunsaturated fatty acids. For industrial applications, the role of breeding aimed at obtaining varieties with certain combination of oil, safflower oleic, linoleic fatty acids. To improve selection, applications of molecular markers in plant breeding and safflower seeds using culture cells and tissues and methods of genetic engineering are found to be promising. Molecular markers for safflower are used to study the phylogenetic relationships and the origin of the Carthamus tinctorius species, to control the commercial use of varieties - the food or the technical direction, and to identify genes associated with specific selection and valuable traits. Use of male gametophyte culture for production of homozygous lines is also promising. Application of genetic engineering techniques may result into development of new safflower varieties with high level of oleic acid and resistant to non-selective herbicide. The problems and prospects of safflower cultivation in Kazakhstan are under discussion.